A bibliometric analysis of housing and settlement research - Sururi, Ahmad (Penerbit Universiti Kebangsaan Malaysia, 2022)
The purpose of the study is to establish a bibliometric analysis as an extensive review of housing and settlement literature. The research was conducted through Google Scholar and Crossref databases using Publish or Perish (PoP) software. Data were analyzed descriptively based on year of publication, author's name, name and country of institution, publication trend, number of publishers, author productivity, number of citations, and affiliation. To map the research, the data were stored in the Mendeley software, exported to RIS format to include all the information related to the articles. The exported data were analyzed using VOSViewer to determine the bibliometric mapping of housing and settlement research. The results of our study conclude that articles published in reputable journals indexed by Scopus with categories Q1, Q2, and Q3 have a significant effect compared to articles published in non-Scopus journals, especially on the number of citations per article. The study also presents the potential topics for future study based on the analysis of keywords with less frequent occurrence.